MAL-PRAKTEK PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PERSPEKTIF KURIKULUM TINGKAT SATUAN PENDIDIKAN (KTSP): STUDI KASUS DI SEKOLAH DASAR NEGERI 01 KECAMATAN TAMBUN SELATAN KABUPATEN BEKASI - Khoir HS, Abdul (Turats, 2012)
This study will discuss about the Mal-Practice in Islamic Education Learning Education: KTSP perspective. A case study in Public Elementary School 01 South Tambun-Bekasi. Educational malpractice is commonly defined as the failure to adequately educate a student. Malpractice has been defined as: - Professional misconduct or unreasonable lack of skill. Failure of one rendering professional service to exercise that degree of skill and learning commonly applied under all the circumstances in the community by the average prudent reputable member of the profession with the result of injury, loss or damage to the recipient of those services or to those entitled to rely upon them. Based on the findings obtained from empirical observations can be put forward some conclusions follow: First, in all that level (elementary, middle and high school) curriculum elements that have not been properly implemented (a) preparation of curriculum development, (b) the development of the syllabus, (c) development, (d) integrated learning, (e) the development of local content, (f) the preparation of the draft assessment of learning outcomes, (g) preparation of students. Secondly, the learning process that takes place using the curriculum in the province of Jambi carried out in accordance with fundamental principles of modern pedagogy and which stresses the importance of planning, implementation, and evaluation right. This can be indicated from (1) completeness of preparation of teachers (Unit Events Lessons/learning scenario), materials (Student Activity Sheet), and the media that teachers use to implement learning activities, (2) compliance with the scenario of learning and teaching varied teaching methods used by teachers, and (3) accuracy in the provision of duty, the utilization of learning resources, and the use of appropriate evaluation tools to get feedback from students. However, from the perspective of quality is still needed guidance